The Role of Jāmiʿ Mosques in Indonesia’s Religious Landscape: A Discourse-Historical Study of Raudlatul Jannah Mosque, Probolinggo, East Java - Sholeh, Adam Wildan; Alfani, Moch. Farich; Rahmasari, Novianti Tri; Mi'rojiaturrohma, Najwa (Indonesian Academy of Social and Religious Research (IASRR), 2025)
The dynamics of mosque empowerment are very diverse, especially in terms of empowering the Muslim community. People often think of mosques as merely places of worship, when in fact mosques can also serve as venues for cultural, social, and even educational activities. The diversity of mosques in Indonesia has unique characteristics, multicultural references, and various typologies from ancient times to the present generation. This study examines various contexts, including historical aspects, the scope of mosque typology research, the relevance of mosques in the development of Islam, and the description of the spread of Islam in the Nusantara region through mosques, particularly in the empowerment of Muslim communities in the Probolinggo region. This research employs a qualitative-descriptive approach with a case study design. Data sources include various forms of evidence, such as interviews, observations, documents, and other visual sources. The collected data was analyzed using an interactive data analysis model, which includes data conditioning, data presentation, and conclusions. The findings show that mosques are a distinctive feature of a region that can provide various relevancies for the Probolinggo community while highlighting the moral aspects inherited from the Prophet Muhammad, which are not limited to verbal advice but also reflect behavior and character examples in accordance with the guidance of the Qur'an. Additionally, it provides community empowerment and typologies of mosques throughout the Probolinggo region.